GE_GERICHTE C/15082/2011 vom 12. Juli 2012 - GE Cour de justice (2012)
BAIL COMMUN ; CONSORITÉ ; CHOSE LOUÉE ; RESTITUTION(EN GÉNÉRAL) ; | CPC.70; CPC.71; CPC.149; CPC.128.3; CPC.68; CPC.147; CPC.148; CPC.135.B; Cst.29.2